Differences In Mental Health Literacy In Pregnant Women Based On Socioeconomic Level At Kembaran 1 Community Health Center, Banyumas Regency - Elisa Putri Elisa Putri; Ema Wahyu Ningrum; Pramesti Dewi (International Journal of Health Engineering and Technology, 2026)
Mental health literacy is an important aspect in maintaining the mental well-being of pregnant women, as it affects their ability to recognize, understand, and make appropriate decisions regarding psychological conditions during pregnancy. Maternal mental health is influenced not only by biological factors but also by socioeconomic factors that play a role in access to information, health services, and support during pregnancy. Differences in socioeconomic status are assumed to affect the level of mental health literacy among pregnant women. This study aimed to determine the relationship between socioeconomic status and mental health literacy among pregnant women in the working area of ​​Kembaran 1 Primary Health Center, Banyumas Regency. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 93 pregnant women selected using consecutive sampling based on inclusion criteria, including pregnant women from all trimesters who were able to read and write and willing to participate, and exclusion criteria including pregnant women with mental disorders or intellectual disabilities. Data were obtained through a mental health knowledge questionnaire and a socioeconomic status questionnaire based on the standards of the Indonesian Ministry of Health, using occupation and income indicators. The results of bivariate statistical analysis showed that there was no relationship between socioeconomic status and mental health literacy among pregnant women at Kembaran 1 Primary Health Center, Banyumas Regency, with ap value of 0.516 (p > 0.05). Although the results indicated no significant relationship, other factors that may influence mental health literacy among pregnant women need to be further investigated to obtain a more comprehensive understanding.